Effect of autotransfusion in HCC surgery on survival and recurrence: a systematic review and meta-analysis - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Ritscher, Emil; Hoffmann, Katrin (Cancers, 2022)
Background: The chronic blood shortage has forced clinicians to seek alternatives to allogeneic blood transfusions during surgery. Due to anatomic uniqueness resulting in a vast vasculature, liver surgery can lead to significant blood loss, and an estimated 30% of patients require blood transfusions in major hepatectomy. Allogeneic transfusion harbors the risk of an immunologic reaction. However, the hesitation to reinfuse a patient’s own blood during cancer surgery is reinforced by the potentiality of reintroducing and disseminating tumor cells into an individual undergoing curative treatment. Two methods of autotransfusions are common: autotransfusion after preoperative blood donation and intraoperative blood salvage (IBS). We aim to investigate the effect of autotransfusion on recurrence and survival rates of patients undergoing surgery for HCC. Methods: The protocol for this meta-analysis was registered at PROSPERO prior to data extraction. MEDLINE, Web of Science and Cochrane Library were searched for publications on liver surgery and blood salvage (autologous transfusion or intraoperative blood salvage). Comparative studies were included. Outcomes focused on long-term oncologic status and mortality. Hazard ratios (HR) estimated outcomes with a fixed-effects model. Risk of bias was assessed using ROBINS-I, and certainty of evidence was evaluated with GRADE. Separate analyses were performed for liver transplantation and hepatectomies. Results: Fifteen studies were included in the analysis (nine on transplantation and six on hepatectomies), and they comprised 2052 patients. Overall survival was comparable between patients who received intraoperative blood salvage (IBS) or not for liver transplantation (HR 1.13, 95% CI [0.89, 1.42] p = 0.31). Disease-free survival also was comparable (HR 0.97, 95% CI [0.76, 1.24], p = 0.83). Autotransfusion after prior donation was predominantly used in hepatectomy. Patients who received autotransfusion had a significantly better overall survival than the control (HR 0.71, 95% CI [0.58, 0.88], p = 0.002). Disease-free survival was also significantly higher in patients with autotransfusion (HR 0.88, 95% CI [0.80, 0.96], p = 0.005). Although overall, the certainty of evidence is low and included studies exhibited methodological heterogeneity, the heterogeneity of outcomes was low to moderate. Conclusion: Autotransfusion, including intraoperative blood salvage, does not adversely affect the overall or disease-free survival of patients with HCC undergoing resection or transplantation. The results of this meta-analysis justify a randomized-controlled trial regarding the feasibility and potential benefits of autotransfusion in HCC surgery.
Gesehen am 09.12.2022